Readers' processing of perceptual perspective and stance. Issue 7 (3rd October 2019) - Dixon, Peter; Bortolussi, Marisa
ABSTRACT: We argue that to understand how readers process narrative, it is necessary to distinguish between psychological stance (i.e., how the narrator evaluates events and characters) and physical perspective (i.e., the angle of view from which events are described). Although these are metaphorically related, the cognitive processes that produce such a connection remain elusive. Here, we provide an analysis of a focal-character heuristic that allows readers to infer stance from physical perspective in third-person narrative. In particular, if readers assume that the story world is described from the physical vantage of a focal character, then that character may be assumed to represent the narrator, and therefore be a reliable source of information about the story world, including psychological evaluations of characters and events. Two experiments support this analysis. In Experiment 1, we used constructed materials. In Experiment 2, we manipulated existing literary short stories. In both experiments, attributing perceptual information to a character increased the reader's adoption of that character's stance.